Detection methods for Pseudomonas aeruginosa: history and future perspective. Issue 82 (8th November 2017) - Tang, Yongjun; Ali, Zeeshan; Zou, Jun; Jin, Gang; Zhu, Junchen; Yang, Jian; Dai, Jianguo
Abstract : The current review summarized and analyzed the development of detection techniques for Pseudomonas aeruginosa over the past 50 years. Abstract : Pseudomonas aeruginosa is a prevalent, opportunistic, Gram-negative bacterium that infects immunocompromised individuals, frequently causing hospital-acquired and community-acquired infections. Currently, Pseudomonas aeruginosa is one of the most widespread and fatal agents among the various causes of nosocomial infections. P. aeruginosa has been associated with increased mortality relative to Staphylococcus aureus or other Gram-negative in bloodstream infections. As few as 10–100 bacilli are capable of colonizing the intestine of critically ill or immunocompromised patients, therefore, early detection of Pseudomonas aeruginosa is particularly important. Here, we have summarized and analyzed the development of detection techniques for Pseudomonas aeruginosa over the past 50 years. We also discuss the prospects for future research on Pseudomonas aeruginosa detection methods in the hope of providing a reference for relevant studies.